Perlindungan Hukum dan Pembinaan Anak Didik Pemasyarakatan Berdasarkan Undang-Undang Nomor 12 Tahun 1995 Tentang Pemasyarakatan - Nurul Chaerani Nur (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2020)
The purpose of this study was to find out the legal protection of prisoner students in the Biak’s Penitentiary based on Law No. 12 of 1995 concerning corrections and to determine the factors that hinder legal protection for the students. This study uses an empirical juridical approach by looking at the applicable legal norms or provisions, then connecting it with the existing facts. The data were obtained through field observations, interviews, and reviewing various required documents. Analysis of the data is descriptive analysis. The results of the study indicate that the legal protection provided to correctional students is to fulfill their rights and provide good guidance according to the students’ needs. The coaching process is carried out in the correctional system and is placed specifically. The type of coaching carried out for correctional students includes mental and social skills development. The factors that hinder the legal protection include the factors of place, human resources, expertise in handling correctional students and cooperation between agencies.